THE IMPACT OF AI ON WORK - Dari Brandon,; Sh.Erdenebileg,; D.Chimgee,; A.Enerel,; A.Bilguun, (Journal of Business and Innovation (Бизнес & Инноваци), 2023)
Artificial intelligence (AI) technologies are developing fast, with many potential benefits for economies, societies and currently influence our lives more than ever before. AI technologies offer the promise of productivity and creating new products and services. The potential of AI to drive change in many employment sectors has revived concerns over automation and the future of work. However, there is consensus that AI will have a disruptive effect on work, with some jobs being lost, others being created, and others changing. According to several economist technological progress will widen the income gap even further and may lead to falling incomes and rising unemployment in large segments of the population. Many economists assume that this increasing automation could lead to a massive increase in unemployment within even the next 10-20 years. So this article aims to review the literature on AI and work, and make conclusion and try to clarify more significant directions in research on AI and work which could be analyzed and discussed further.